Potential Protective Effects of Naringin on Oculo-Pulmonary Injury Induced by PM10 (Wood Smoke) Exposure by Modulation of Oxidative Damage and Acetylcholine Esterase Activity in a Rat Model - Jacob K. Akintunde, PhD; Joseph B. Abioye, MPH; Owen N. Ebinama, MPH (Elsevier, 2020)
ABSTRACT: Background: Millions of households in the world depend on wood and biomass for cooking and heating. This dependence leads to undesirable toxic effects, such as ocular and pulmonary toxicity. Objectives: The present study examined the potential oculoprotective and pulmonary protective activity of naringin (NRG), a naturally occurring flavonoid, against wood smoke (WS)-induced toxicity in a rat model. Methods: Forty-eight adult male albino rats were randomly distributed into six (n=8) groups. All rats were fed, given water, and observed for 21 days, Group I (control) received only distilled water and no WS exposure, Group II was exposed to WS, Group III was exposed to WS and given 50 mg/kg/d α-tocopherol (vitamin E), Group IV was exposed to WS and given 80 mg/kg/day NRG, Group V was administered only 80 mg/kg/d NRG only, and Group VI was administered only 50 mg/kg/d vitamin E. WS exposure was for 20 min/d. The effect of NRG treatment on acetylcholinesterase activity, nitric oxide radical production, malondialdehyde level, and antioxidant enzymes (ie, superoxide dismustase and catalase) in WS-exposed rats was examined. Results: Subchronic (21 day) exposure to WS induced ocular and pulmonary toxicity manifested by the infiltration of parenchyma, atrophy, and inflammation of the cells, which was correlated with alterations in antioxidant enzyme concentrations. Cell damage was associated with an increase in acetylcholinesterase activity and nitric oxide radical concentrations. The toxicity triggered by WS was modulated by the coadministration of NRG. Conclusion: These results suggest that NRG treatment may be useful to reduce WS-induced oxidative stress and related ocular and pulmonary damage in rats. (Curr Ther Res Clin Exp. 2012; 73:XXX-XXX)